Bioinformatic identification of ClpI, a distinct class of Clp unfoldases in Actinomycetota - Jiang, Jialiu; Schmitz, Karl R. (Frontiers in Microbiology, 2023)
All clades of bacteria possess Hsp100/Clp family unfoldase enzymes that contribute to aspects of protein quality control. In Actinomycetota, these include ClpB, which functions as an independent chaperone and disaggregase, and ClpC, which cooperates with the ClpP1P2 peptidase to carry out regulated proteolysis of client proteins. We initially sought to algorithmically catalog Clp unfoldase orthologs from Actinomycetota into ClpB and ClpC categories. In the process, we uncovered a phylogenetically distinct third group of double-ringed Clp enzymes, which we term ClpI. ClpI enzymes are architecturally similar to ClpB and ClpC, with intact ATPase modules and motifs associated with substrate unfolding and translation. While ClpI possess an M-domain similar in length to that of ClpC, its N-terminal domain is more variable than the strongly conserved N-terminal domain of ClpC. Surprisingly, ClpI sequences are divisible into sub-classes that either possess or lack the LGF-motifs required for stable assembly with ClpP1P2, suggesting distinct cellular roles. The presence of ClpI enzymes likely provides bacteria with expanded complexity and regulatory control over protein quality control programs, supplementing the conserved roles of ClpB and ClpC.